Immunogenicity and reactogenicity of heterologous immunization against SARS CoV-2 using Sputnik V, ChAdOx1-S, BBIBP-CorV, Ad5-nCoV, and mRNA-1273 - Laboratorio SeVa Group (2022)
Heterologous vaccination against coronavirus disease 2019 (COVID-19) provides a rational strategy to rapidly increase vaccination coverage in many regions of the world. Although data regarding messenger RNA (mRNA) and ChAdOx1 vaccine combinations are available, there is limited information about the combination of these platforms with other vaccines widely used in developing countries, such as BBIBP-CorV and Sputnik V. Here, we assess the immunogenicity and reactogenicity of 15 vaccine combinations in 1,314 participants. We evaluate immunoglobulin G (IgG) anti-spike response and virus neutralizing titers and observe that a number of heterologous vaccine combinations are equivalent or superior to homologous schemes. For all cohorts in this study, the highest antibody response is induced by mRNA-1273 as the second dose. No serious adverse events are detected in any of the schedules analyzed. Our observations provide rational support for the use of different vaccine combinations to achieve wide vaccine coverage in the shortest possible time.